Matriz de dotación hospitalaria para la infraestructura nueva del Hospital Francisco de Paula Santander E.S.E (2024)
This degree work is carried out in the form of a business internship at the Francisco de Paula Santander E.S.E Hospital in the municipality of Santander de Quilichao (Department of Cauca) and arose from the need to project a hospital provision matrix for the new physical infrastructure of the hospital. The degree work is supported by the existing agreement between the Hospital and the Antonio Nariño University. To comply with the objectives set out in the work, technical visits were made to the hospital, advice was received from the professionals in charge of the project to recognize the current need for hospital equipment and verify the structural design of the matrix. The content in the matrix was incorporated according to what was proposed in resolutions 2053 of 2019 and 3100 of 2019 and the preliminary results of the obsolescence index provided by the E.S.E. Also, a repository of technical sheets of hospital equipment from different brands was created to access the information in an organized manner and a comparative table of prices offered was prepared based on the quotes made by the E.S.E. All these activities were carried out in the company of the support professionals in the project. It is expected that the contribution of this internship, which within the structuring of the project is in the planning and selection phase, will encourage compliance with the technical feasibility of the project in relation to what is established by regulations, guaranteeing safety, quality and efficiency of the provision in the provision of health services of the E.S.E in the new infrastructure.